Public Space Office Hours. Issue 3 (3rd July 2021) - Glynn-Adey, Parker
Abstract: In this teaching commentary, we describe a re-positioning of office hours from private faculty offices to public spaces such as student centers and cafes. We argue that this shift promotes faculty-student interaction, lowers barriers to help-seeking behavior, and facilitates collaboration among students. We highlight the power dynamics of private office hours, and argue that public office hours support English language learners and other marginalized populations in academia.